Determination of suitable thin layer drying curve model for some vegetables and fruits - Akpinar, EK (Elsevier Sci Ltd, 2006)
This study presents a mathematical modeling of thin layer drying of potato, apple and pumpkin slices in a convective cyclone dryer. In order to estimate and select the appropriate drying curve equation, 13 different models, which are semi-theoretical and/or empirical, were applied to the experimental data and compared according to their coefficients of determination (r, X-2), which were predicted by non-linear regression analysis using the Statistica Computer Program. Moreover, the effects of drying air temperature, velocity and sample area on the model constants and coefficients were also studied by multiple regression analysis. Consequently, of all the drying models, a semi-theoretical Midilli-Kucuk model was selected as the best one, according to r and X-2 (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: drying; thin layer; mathematical modelling